(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: FNAC is the first diagnostic step in patients with lymphadenopathy because of its simplicity and minimal invasive nature which helps to confirm the clinical suspicion. A definite specific diagnosis may not be possible in a few cases but a categorization of disease and differential diagnosis can help suggest the most efficient further investigations, saving time and resources. The aim of this study was to ascertain the system’s applicability and precision in the diagnosis of lymph node cytology. Material and methods: A retrospective cross-sectional study on lymph node cytology samples collected between January 2024 and June 2024, categorizing results into five groups (L1-L5) according to the Sydney System. Cytological findings were validated against histopathological results and relevant clinical data that prompted FNA procedures. Diagnostic performance was evaluated using metrics such as sensitivity, specificity, predictive values, and malignancy risk estimates. Results: 60 cases were evaluated by FNAC. Out of this 44 were benign cases, 16 cases were of Reactive lymphadenitis, 24 cases of Granulomatous/Tuberculous lymphadenitis and 4 cases were of Acute suppurative lymphadenitis. Out of 16 malignant cases, 1 case was of Non Hodgkins lymphoma, 2 case was of Hodgkins lymphoma and 13 cases were of metastatic carcinoma. Conclusion: The Sydney system was used for clinicopathological diagnosis of patients presenting with lymphadenopathy and was found to be a reliable tool for evaluation of risk of malignancy and its subsequent management of the patient.